2016
DOI: 10.1002/slct.201601196
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thieno[2,3‐d]pyrimidines via Microwave‐Assisted Thermolysis of 1‐(Thiophene‐2‐yl)‐1H‐tetrazoles

Abstract: A selective and efficient method for the synthesis of unusual thieno[2,3‐d]pyrimidines incorporating two thiophene rings via thermal reactions of 1‐(thiophene‐2‐yl)‐1H‐tetrazoles is reported. Microwave‐assisted thermolysis of 1‐(thiophene‐2‐yl)‐1H‐tetrazoles at 160 °C in a water/toluene (2:1) solvent system afforded thieno[2,3‐d]pyrimidines in moderate to good yield (up to 66 %) as single products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As mentioned in the Introduction, N -arylimidoylnitrenes are frequently found to cyclize to benzimidazoles and related compounds. Thus flash vacuum pyrolysis of 1-phenyltetrazoles yields benzimidazoles (Scheme ). The DFT calculations confirm cyclization of the OSS imidoylnitrene 10d to 3a H -benzimidazole 12d .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the Introduction, N -arylimidoylnitrenes are frequently found to cyclize to benzimidazoles and related compounds. Thus flash vacuum pyrolysis of 1-phenyltetrazoles yields benzimidazoles (Scheme ). The DFT calculations confirm cyclization of the OSS imidoylnitrene 10d to 3a H -benzimidazole 12d .…”
Section: Results and Discussionmentioning
confidence: 99%
“…There is very little direct spectroscopic evidence for the existence of imidoylnitrenes, but it is noted that weak, broad absorptions observed around 520 nm on laser flash photolysis of 5-phenyltetrazole and 1-methyl-5-phenyltetrazole may be due to the benzimidoylnitrenes . Despite the shortage of direct evidence, imidoylnitrenes are very frequently postulated as reactive intermediates in pyrolyses and photolyses of 1-aryltetrazoles 6′ , where they typically cyclize onto the benzene rings to afford benzimidazoles and related compounds. Ring cleavage reactions with formation of carbodiimides or cyanamides have also been thoroughly investigated. …”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to try to overcome this problem by using the falling-solid flash vacuum pyrolysis methodology . Evidence for the formation of carbodiimides 334 as intermediates en route to compounds 335 in microwave-assisted solution thermolyses was also adduced. , …”
Section: Azidesmentioning
confidence: 99%
“…35 Evidence for the formation of carbodiimides 334 as intermediates en route to compounds 335 in microwave-assisted solution thermolyses was also adduced. 287,288 The imidoyl azide valence tautomers of the tetrazoles are not often observed in this chemistry, but they were observed in the reactions described in Scheme 46. The polymethylenetetrazoles have revealed very interesting pyrolysis chemistry.…”
Section: Imidoyl Azides [Rc(nr′)−n 3 ] and Imidoylnitrenes [R(cnr′)−n]mentioning
confidence: 99%
“…Soares et al [ 36 ] reported a selective plus proficient technique for the construction of thieno[2,3‐d]pyrimidine derivatives as shown in Scheme 30. The intermediates for unusual transformation were synthesized from 2‐aminothiophene‐3‐carboxylates 92, triethyl orthoformate, and sodium azide in glacial acetic acid.…”
Section: Synthetic Strategiesmentioning
confidence: 99%